EFEKTIVITAS SLOW DEEP BREATHING DENGAN ALAT TILUTAR ORAIN TERHADAP PENURUNAN NYERI PEMASANGAN INFUS PADA ANAK USIA 4 -7 TAHUN - Rina Zulistin; Bayhakki Bayhakki; Sri Utami (Jurnal Ners Indonesia, 2023)
The purpose of this study is to examine the effect of blowing tilutar orain against the reductionof pain during IV insertion in children aged 4-7 years old. This study quantitative research byusing research design of quasy eksperiment through research design approach of posttest onlynon equivalent control group design. The are two groups in this study which are theexperimental group which is given the test and the control group which is not given the test.The participants of this study are all of children aged 4-7 years. In the emergency departementof Hospital Awal Bros Sudirman, Awal Bros Ahmad Yani, and Awal Bros Panam that areinserted of infusion.The sample of 54 person is taken by using purposive sampling which isdevided into both experimental and control groups. The instrument which is used is observationsheet by using pain scale of FLACC. Used is Mann-Whitney Test. The result show that there isinfluence in blowing tilutar orain to decrease of pain while inserting infusion in children aged4-7 years, ( p value score 0,000 which means value < 0,05).